2006
DOI: 10.1111/j.1551-2916.2005.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Characteristics of Nd(Zn1/2Ti1/2)O3 Ceramics at Microwave Frequencies

Abstract: The microwave dielectric properties and the microstructures of Nd(Zn1/2Ti1/2)O3 (NZT) ceramics prepared by the conventional solid‐state route have been studied. The prepared NZT exhibited a mixture of Zn and Ti showing 1:1 order in the B‐site. The dielectric constant values (ɛr) saturated at 29.1–31.6. The quality factor (Q×f) values of 56 700–170 000 (at 8.5 GHz) can be obtained when the sintering temperatures are in the range of 1300°–1420°C. The temperature coefficient of resonant frequency τf was not sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…A maximum Q Â f value of 165,300 GHz was obtained for Nd(Zn 1/2 Ti 1/2 )O 3 ceramics sintered at 1360 1C for 4 h with a cooling rate of 1 1C/min. The values of Q Â f measured for all compositions are about a factor of (4-6) higher than the value reported previously by Iddles et al [14], but almost the same as those reported by Tseng et al [9]. It is well known that there are many factors such as density, secondary phase, grain size and cation ordering to influence microwave dielectric loss of a material [21].…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…A maximum Q Â f value of 165,300 GHz was obtained for Nd(Zn 1/2 Ti 1/2 )O 3 ceramics sintered at 1360 1C for 4 h with a cooling rate of 1 1C/min. The values of Q Â f measured for all compositions are about a factor of (4-6) higher than the value reported previously by Iddles et al [14], but almost the same as those reported by Tseng et al [9]. It is well known that there are many factors such as density, secondary phase, grain size and cation ordering to influence microwave dielectric loss of a material [21].…”
Section: Resultssupporting
confidence: 71%
“…Among these materials, Nd(Zn 1/2 Ti 1/2 ) O 3 ceramics were found to possess better microwave dielectric properties (ε r =31.6, Q Â f=170000 GHz and τ f = À 42 ppm/ o C) after sintering at 1330 1C for 4 h with a cooling rate of 10 1C/ min [9]. However, the maximum available from a reported UK patent was around 27,000 GHz, with maximum ε r of 27.5 when Nd(Zn 1/2 Ti 1/2 )O 3 ceramics were sintered at 1500 1C for 8 h [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As observed in Fig. 6, the τ f value varied toward A breaking point appears at 1300 • C and the variation of τ f becomes downward due to the decrease of ZnTiO 3 phase resulted from Zn evaporation as the sintering temperature rises above 1300 • C [15]. The Zn position was most likely occupied by exceeding Mg to form MgTiO 3 .…”
Section: Microwave Dielectric Propertiesmentioning
confidence: 76%
“…The LTCC technology offers the possibility of the monolithic multilayer structures with buried passive components as a key development for integrated electronic components including IC packaging radar and antennas [1][2][3]. As an LTCC substrate material, dielectric ceramics have been investigated to meet the target characteristics such as low dielectric constant and high quality factor [4][5][6].…”
Section: Introductionmentioning
confidence: 99%